2019 IEEE Automatic Speech Recognition and Understanding Workshop (ASRU) 2019
DOI: 10.1109/asru46091.2019.9003891
|View full text |Cite
|
Sign up to set email alerts
|

SLU for Voice Command in Smart Home: Comparison of Pipeline and End-to-End Approaches

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
0
12
0
2
Order By: Relevance
“…Note that so far, the direct comparison of E2E-SLU with pipeline approaches are mainly limited to baselines developed on the same dataset, e.g. a multistage neural model in which the two stages that correspond to ASR and NLU are trained independently, but using the same training data (Desot et al, 2019;Haghani et al, 2018). We follow a different approach, which, as we argue, is closer to the 6 The official script for analysis and evaluation will be released with SLURP at https://github.com/ pswietojanski/slurp.…”
Section: Methodsmentioning
confidence: 99%
“…Note that so far, the direct comparison of E2E-SLU with pipeline approaches are mainly limited to baselines developed on the same dataset, e.g. a multistage neural model in which the two stages that correspond to ASR and NLU are trained independently, but using the same training data (Desot et al, 2019;Haghani et al, 2018). We follow a different approach, which, as we argue, is closer to the 6 The official script for analysis and evaluation will be released with SLURP at https://github.com/ pswietojanski/slurp.…”
Section: Methodsmentioning
confidence: 99%
“…On top of that, our correlation tests in Section 5.3 showed that perfect ASR is not necessary to obtain good E2E SLU performance. It is, however, essential in the case of a pipeline approach as we have demonstrated in Desot et al (2019b) for intent prediction and in Desot et al (2019a) for concept prediction. This answers our first question and confirms the state-of-the-art: the E2E model reduces the cascade of error effect.…”
Section: Discussionmentioning
confidence: 99%
“…The E2E approach as outlined in Desot et al (2019a) was based on the ESPnet ASR toolkit (Watanabe et al, 2018). It integrates the Kaldi data preparation, extracts Mel filter-bank features, and combines Chainer and PyTorch deep learning tools (Tokui et al, 2015;Paszke et al, 2017).…”
Section: End-to-end Slumentioning
confidence: 99%
See 1 more Smart Citation
“…Note that so far, the direct comparison of E2E-SLU with pipeline approaches are mainly limited to baselines developed on the same dataset, e.g. a multistage neural model in which the two stages that correspond to ASR and NLU are trained independently, but using the same training data (Desot et al, 2019;Haghani et al, 2018). We follow a different approach, which, as we argue, is closer to the real-life application scenario: We use competitive ASR systems and state-of-the-art NLU systems.…”
Section: Methodsmentioning
confidence: 99%